Perceptions of postpartum women regarding the role of physiotherapy in childbirth preparation: A qualitative study (Research, Society and Development, 2024)
Introduction: Pregnancy is considered a physiological process. As a result, the body undergoes adaptations that can lead to pain and discomfort, affecting the quality of life. During this phase, physiotherapy helps alleviate pain, providing pelvic muscle stretching and strength training, promoting a quality pregnancy and labor. Objective: To analyze postpartum women's perception of the role of physiotherapy in preparing for childbirth. Methods: This is a qualitative study conducted by Research Group on Pelvic Floor Dysfunction Studies. The sample was non-probabilistic, convenience, and intentional, consisting of postpartum women who participated in the research project during pregnancy and agreed to participate in the study. Data collection was carried out after childbirth through an online questionnaire. Data analysis was performed using Bardin's content analysis method. Results: The sample consisted of 17 postpartum women, and according to their perception, the role of physiotherapy in preparing for childbirth contributed to a quality childbirth experience with reduced obstetric complications, decreased reported discomfort, and, for the most part, a pleasant childbirth experience in line with their expectations. Conclusion: The study demonstrated that physiotherapy during pregnancy assisted in labor and improved the quality of life by reducing muscle pain and other discomforts in postpartum women.